Molecular Mechanism of Caffeine-Aspirin Interaction in Kopi Balur 1 as Anti-Inflammatory Agent: A Computational Study - Viol Dhea Kharisma1,2, Arif Nur Muhammad Ansori2,3, Amaq Fadholly3 , Teguh Hari Sucipto4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Balur treatment (BT) is a method that works to remove toxins in the form of free radicals released via theskin. One of the remedies used is Kopi Balur 1 (KB1) which contains aspirin and caffeine used duringthe BT, so that KB1 is believed to have the potential to reduce or inhibit the occurrence of inflammatoryprocesses in the body. Therefore, we investigate the interactions that occur between ligands and proteins,predict the action mode of caffeine-aspirin contained in KB1 as an anti-inflammatory agent, and modelingthe 3D structure of pro-inflammatory proteins in the human body. The target compound, aspirin-caffein,was obtained from a database, then used to identify the pathway on the STITCH webserver, then the targetprotein was obtained and modeled in 3D using the SWISS-MODEL webserver, and the structures obtainedwere represented in PyMol software. In sum, the aspirin-caffeine ligand complex contained in KB1 has thepotential as an anti-inflammatory agent in the human body via the molecular mechanism of binding andinhibiting the biological activity of proinflammatory proteins, i.e. PTGS1, PTGS2, and ADOR2A.